EVALUASI PROGRAM PEMBELAJARAN PENDIDIKAN JASMANI DI PONDOK PESANTREN MU’ALIMIN MUHAMADIYA H DAERAH ISTIMEWA YOGYA KARTA - Lalu Armin Suhaidin (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2015)
AbstractThis research purposed to evaluated the program of physical education learning that was viewed from the componentswere (1) context (2) input (3) process and (4) the school output. The context component were consists of programand purpose. The input component were consists of syllabus, lesson material, media or tool of learning, teacher,student, infrastructure and the condition of learning environment. The component of process were consists of thereadiness of physical education learning, implementation and evaluation. Whereas, the product component was theachievement or student’s value on the physical education learning in pondok pesantren Mu’alimin MuhammadiyahYogyakarta. This research was study of evaluation by using qualitative analysis and quantitative descriptive waspurposed to evaluate the physical education program. The population of study was all students of junior high school(VII and VIII class) and senior high school (X and XI class) of pondok pesantren Mu’alimin Muhammadiyah Yogyakartawhich amount 832 students. The sample of research were taken as much as 276 students, consists of 149 studentsof junior high school and 127 students of senior high school. The data of research was gathered through interview,observation, documentation and questioner, the result of this research founded that the management of physicaleducation learning program, if reviewed from the input form of the availability of the lesson material media, learningmedia, teacher, infrastructure and the condition of environment, if was viewed from the process in good category. Withthe average score was 2.60 (1-4 scale) according to student and 3.05 according to teacher was in good category. Ifwas seen from the achievement product or student’s value proved that the physical education was in good category.Key Word: evaluation, context, input, process, product, learning, physical education.AbstrakPenelitian ini bertujuan untuk mengevaluasi program pembelajaran pendidikan jasmani yang ditinjau dari komponenkomponenberikut: (1) konteks, (2) input, (3) proses, dan (4) output sekolah. Komponen konteks terdiri atas programdan tujuan. Komponen iput terdiri atas silabus, materi pelajaran, media atau alat pembelajaran, guru, mahasiswa,infrastruktur dan kondisi lingkungan belajar. Komponen proses terdiri atas kesiapan belajar pendidikan jasmani,pelaksanaan dan evaluasi. Sedangkan, komponen produk adalah prestasi atau nilai siswa pada pembelajaranpendidikan jasmani di Pondok Pesantren Muallimin Muhammadiyah Yogyakarta. Penelitian ini merupakan penelitianevaluasi dengan menggunakan analisis data kualitatif dan deskriptif kuantitatif yang bertujuan untuk mengevaluasiprogram pendidikan jasmani. Populasi penelitian adalah seluruh siswa sekolah SMP (kelas VII dan VIII) dan SMA(kelas X dan XI) dari Pondok Pesantren Muallimin Muhammadiyah yang berjumlah 832 siswa. Sampel penelitiandiambil sebanyak 276 siswa, terdiri atas 149 siswa dari SMP dan 127 siswa SMA. Data penelitian dikumpulkanmelalui wawancara, observasi, dokumentasi dan kuesioner, hasil penelitian ini ditemukan bahwa pengelolaan programpembelajaran pendidikan jasmani, jika ditinjau dari input ketersediaan media bahan pelajaran, media pembelajaran,guru, infrastruktur dan kondisi lingkungan, jika dilihat dari proses dikategorikan dalam kategori baik. Dengan skorrata-rata 2.60 (1-4 skala) menurut siswa dan 3.05 menurut guru masuk dalam kategori baik. Jika dilihat dari produkprestasi atau nilai siswa terbukti bahwa pendidikan jasmani masuk dalam kategori baik.Kata kunci: evaluasi, konteks, input, proses, produk, pembelajaran, pendidikan jasmani.